2005
DOI: 10.2166/ws.2005.0034
|View full text |Cite
|
Sign up to set email alerts
|

Application of MIEX® pre-treatment for ultrafiltration membrane process for NOM removal and fouling reduction

Abstract: In this study, pretreatment of organic matters with MIEX® was evaluated using bench-scale experimental procedures on three organic matters to determine its effect on subsequent UF or MF membrane filtration. For comparison, a coagulation process was also used as a pretreatment of UF or MF membrane filtration. Moreover, the membrane fouling potential was identified using different fractions and molecular weights (MW) of organic matter. From the removal property of MW organic matter by the coagulation process for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Some other studies have also shown that a combination of MIEX and coagulation resulted in decreased fouling of UF or MF membranes when treating NOM. [21][22][23] Our study appears to be the first to come to the same conclusion when dealing with wastewater effluent. Although fouling was also decreased after sweep floc coagulation with alum, the much higher concentration of new solids could result in operational problems, not only in dead-end applications but also in recirculating systems.…”
Section: Pretreatment Followed By Mf or Ufsupporting
confidence: 60%
See 1 more Smart Citation
“…Some other studies have also shown that a combination of MIEX and coagulation resulted in decreased fouling of UF or MF membranes when treating NOM. [21][22][23] Our study appears to be the first to come to the same conclusion when dealing with wastewater effluent. Although fouling was also decreased after sweep floc coagulation with alum, the much higher concentration of new solids could result in operational problems, not only in dead-end applications but also in recirculating systems.…”
Section: Pretreatment Followed By Mf or Ufsupporting
confidence: 60%
“…[11] Other studies have shown that a combination of coagulation and MIEX resulted in decreased fouling in MF or UF. [21][22][23] In this study, we investigated a complete-mix process using MIEX.…”
Section: Introductionmentioning
confidence: 99%
“…9) which shows the surface foulants are clearly reduced with pre-treatment and that alum provided a significant improvement. In comparing coagulation and MIEX ® pre-treatment for ultrafiltration, Son et al [37] also observed that MIEX ® was less effective for reduction of fouling due to lesser removal of high MW organic matter. For the treatments that included PAC, some residual particulates from PAC can also be seen which is consistent with the obtained resistance data and the work of Matsui et al [24] with submicrometre PAC on microfiltration.…”
Section: Flat Sheet Fouling Experimentsmentioning
confidence: 99%
“…Anion exchange resin has been investigated as a means of improving membrane performance by removing a significant fraction of organic matter from drinking water sources [19][20][21]. The small resin particles provide a high-surface area for the adsorption of lower MW and negatively charged organic components [19].…”
Section: Introductionmentioning
confidence: 99%
“…The small resin particles provide a high-surface area for the adsorption of lower MW and negatively charged organic components [19]. The effects of anion exchange treatment on membrane fouling are dependent on the properties of source water, types of pre-treatment combination and membranes [20,21]. Only one application was found where anion exchange resin was used in wastewater treatment, and this related to a submerged membrane bioreactor system with synthetic wastewater [22].…”
Section: Introductionmentioning
confidence: 99%